MIKROENCAPSULATION OF CROSSLINKED CHITOSAN AND ITS ADSORPTIVITY TEST ON REMAZOL YELLOW FG 6 - Kusumaningsih, Triana; Pranoto, Pranoto; Handayani, Desi Suci; Kusuma Astuti, Dian Endah (Alchemy Jurnal Penelitian Kimia, 2013)
Synthesis of adsorbent by crosslink and microencapsulation modification produce modified chitosan had been done. The product was used as adsorben forÂ Remazol Yellow FG 6Â dye. The adsorptivity test was carried out by comparing the ability of chitosan, crosslinked chitosan and mikroencapsulation of crosslinked chitosan to adsorbremazol yellow FG 6Â dye at pH 11, 15 ppm of dyeâs concentration, and at various contact times.The result shows that the crosslinked chitosan adsorbsÂ Remazol Yellow FG 6Â dye 3.99 times higher than the unmodified chitosan. Meanwhile, the microcapsules containing crosslinked chitosan adsorbÂ Remazol Yellow FG 64.00 times higher than unmodified chitosan. The adsorption performance of each prepared material was determined from UV-Vis absorbance analysis. Although the adsorption performance of the microcapsules containing crosslinked chitosan is almost similar to the crosslinked chitosan, however the microcapsules have shorter optimum contact time and also more stable than the crosslinked chitosan. It shows that the modification of chitosan with crosslinking and microencapsulation process improve its adsorptivity and stability.